The interactive effects of abusive supervision and entitlement on emotional exhaustion and co‐worker abuse. Issue 4 (26th August 2013) - Wheeler, Anthony R.; Halbesleben, Jonathon R. B.; Whitman, Marilyn V.
Abstract : In this study, we examine the relationship between employee perceptions of supervisor abuse, emotional exhaustion, psychological entitlement, and subsequent co‐worker abuse. We hypothesize that higher levels of employee psychological entitlement moderate the abusive supervisor – emotional exhaustion relationship – and this interaction mediates the abusive supervision – co‐worker abuse relationship. Using multilevel‐moderated mediation analysis to analyse day‐level survey data from a lagged panel design across five working days from 132 working adults and their co‐workers across multiple industries, we found support for our hypothesized model. We discuss implications for theory, future research, and management practice that result from our study. Practitioner points: Psychologically entitled employees who perceive more abusive supervision are more emotionally exhausted and more likely to abuse their co‐workers; therefore, organizations need to identify patterns indicative of these types of employees. Stressed environments likely exacerbate these relationships, and organizations might consider regular workforce surveys assessing employee emotional exhaustion, which is a trigger for harmful employee work behaviours.